Lumbar lordosis does not correlate with pelvic incidence in the cases with the lordosis apex located at L3 or above - Tono, Osamu; Hasegawa, Kazuhiro; Okamoto, Masashi; Hatsushikano, Shun; Shimoda, Haruka; Watanabe, Kei; Harimaya, Katsumi (European spine journal, 2019)
Purpose To test the hypothesis that the relationship between PI and L1–S1 lumbar lordosis (LL) is always positive, even in cases with different lumbar sagittal profiles. Methods Standing whole-spine sagittal alignment was measured with EOS system in 100 healthy adults (46 men, 54 women, mean age 40.9 years). The apex of lumbar lordosis was defined as the most anterior lumbar vertebra or intervertebral disk from the gravity line determined by a force plate measurement. Subjects were stratified into three groups: the upper group with an apex between L1 and L3 ( UppA , n = 19), the middle group with an apex from L3/4 to L4/5 ( MidA , n = 67), and the lower group with an apex at L5 or below ( LowA , n = 14). PI, PT, SS, thoracic kyphosis (TK), LL, SVA, T1 pelvic angle, and knee flexion angle were compared between the groups. The correlation between LL and PI in each group was also compared. Results PI and SS differed significantly between the three groups, and LL was significantly different between LowA and MidA and UppA . TK and KF did not differ significantly between groups. LL and PI were significantly positively correlated in the MidA and LowA groups, but not in the UppA group. Conclusion Contrary to the hypothesis, the correlation coefficient between PI and LL was not significant in the cases with apex above L3, suggesting that the relationship between PI and LL is not always constant, and whole sagittal alignment should be taken into account. Graphical abstract These slides can be retrieved under Electronic Supplementary Material.